2003
DOI: 10.1051/forest:2003035
|View full text |Cite
|
Sign up to set email alerts
|

Stability of transgene expression in poplar: A model forest tree species

Abstract: -We evaluated the stability of trangene expression in a hybrid poplar (Populus tremula ´ P. alba) clone transformed with constructs carrying a reporter gene (uidA) under the control of either a constitutive (35S) or a vascular-specific promoter. Analyses of transgene expression by GUS fluorometry and histochemistry was performed on several hundreds of trees, originating from 44 different transgenic lines, grown under in vitro, greenhouse and field conditions. While important variations in expression levels occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…In a study of 40 independent transgenic hybrid cottonwood (P. trichocarpa × P. deltoides) plants that expressed herbicide resistance and GUS reporter genes and were monitored for four years under field conditions, only one showed instability of the transgene expression (Meilan et al, 2002). Similar results were obtained in a study of 20 transgenic events that expressed the GUS reporter gene under 35S and xylem-specific promoters (Hawkins et al, 2003). In the same study stable transgene expression was found under in vitro, greenhouse and field conditions and the expression was not affected by stress treatments.…”
Section: Transformation and Poplarssupporting
confidence: 74%
“…In a study of 40 independent transgenic hybrid cottonwood (P. trichocarpa × P. deltoides) plants that expressed herbicide resistance and GUS reporter genes and were monitored for four years under field conditions, only one showed instability of the transgene expression (Meilan et al, 2002). Similar results were obtained in a study of 20 transgenic events that expressed the GUS reporter gene under 35S and xylem-specific promoters (Hawkins et al, 2003). In the same study stable transgene expression was found under in vitro, greenhouse and field conditions and the expression was not affected by stress treatments.…”
Section: Transformation and Poplarssupporting
confidence: 74%
“…However, analysis of the instable/stable transgene expression in tree is more problematic than in crop plants (kumer, 2000a). Several studies have been conducted in perennial plants, including poplar trees, over multiple seasons and after vegetative propagation (GalloMeagher and Irvine, 1996;Bettany et al, 1998;Cervera et al, 2000;Kumar and Fladung, 2001;Meilan et al, 2002;Hawkins et al, 2003;Leibbrandt and Snyman, 2003) but these studies have given conflicting result (Li, et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies did demonstrate that long term culture of transgenic plants in field affected the expression of the transgene (Kumar and Fladung, 2001;Hawkins et al, 2003). This is important in the application of transgenic tree species.…”
Section: Introductionmentioning
confidence: 99%
“…These are genomic regions, often located near the centromer of a chromosome, which are not expressed. However, field experiments with trees transformed with marker genes showed that, when the transgene is inserted as single copy in euchromatin regions, silencing was a rare event in the investigated poplars (Hawkins et al 2003, Fladung et al 2004). …”
Section: Risks and Potentialsmentioning
confidence: 99%